High-Performance Cu1.8Se Nanosheets for Dual-Sensing: H2O2 Electrochemical Detection and SERS Substrate - Ying-Chu Chen; Michael Chen; Yu-Kuei Hsu (Nanomaterials)
A facile fabrication method was developed for the growth of Cu1.8Se nanosheets (NSs) on a Cu foil substrate, enabling dual-functionality as an electrochemical sensor for H2O2 and an active surface-enhanced Raman scattering (SERS) substrate. The process involved the preparation of Cu(OH)2 nanowires (NWs) via electrochemical oxidation, followed by chemical conversion to Cu1.8Se through a selenization process. The morphology, composition, and microstructure of the resulting Cu1.8Se NSs were systematically characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The Cu1.8Se NSs exhibited excellent electrocatalytic activity for H2O2 reduction, achieving a notably low detection limit of 1.25 μM and demonstrating rapid response and high sensitivity with a linear relationship in amperometric detection. Additionally, SERS experiments using Rhodamine B as a probe molecule and the Cu1.8Se NS/Cu foil as a substrate displayed outstanding performance, with a detection limit as low as 1 μM. The flower-like structure of the Cu1.8Se NSs exhibited linear dependence between analyte concentration and detection signals, along with satisfactory reproducibility in dual-sensing applications. These findings underscore the scalability and potential of this fabrication approach for advanced sensor development.